Utilization of Outpatient Mental Health Services During and After The COVID-19 Pandemic - Hayek, Michelle; Park, Sulki; Lawley, Mark; Bovin, Michelle; Kum, Hye-Chung (International Journal of Population Data Science, 2024)
Objective and Approach This study examines the impact of COVID-19 on outpatient mental health (OP-MH) service use and assesses the role of telehealth on OP-MH service patterns. Using the 5% national sample of Medicare beneficiaries, the intervention group was defined as those newly diagnosed with a MH condition in 2019 (no MH diagnosis 2 years prior) with a 2-year study period of 2020-2021. The comparison group included non-overlapping individuals newly diagnosed in 2017 with a study period of 2018-2019. The OP utilization patterns were examined over the 2 years post-diagnosis and compared across MH diagnostic categories, including schizophrenia, bipolar, depression, anxiety, trauma-related, and substance-use disorders. Results The intervention group observed a significant reduction in MH utilization in March-April 2020 compared to the matched sample. While patients with schizophrenia and bipolar disorders saw a return to normal patterns by May 2020, those with depression, anxiety, trauma-related, and substance-use disorders continued to exhibit significant reductions in MH utilization post-COVID-19. The intervention group demonstrated a significant increase in telehealth usage, transitioning from 1% pre-COVID-19 to a peak of ~60% during the pandemic. This trend gradually decreased, reaching an average of 30% by the end of 2021 across all conditions. Conclusions and Implications This study underscores the impact of the pandemic on OP-MH utilization and emphasizes the potential of telehealth in improving access to care to meet OP-MH needs. Further, the results highlight the differences in OP-MH utilization across diagnostic categories and the relative benefit of telehealth options for these conditions.